INTERNALISASI NILAI-NILAI AKHLAKUL KARIMAH DALAM MENINGKATKAN SPIRITUAL SISWA - Chandra Diyah Ningrum; Muchamad Suradji (Program Studi Pendidikan Agama Islam Fakultas Agama Islam Universitas Islam Darul 'Ulum Lamongan, 2021)
The purpose of this research is to find out how the process of internalizing the moral values ​​of madrasah diniyah Ar-Rosyid and to find out the results of the process of internalizing the values ​​of akhlakul karimah in improving the spirituality of students at madrasah diniyah Ar-Rosyid Ds. Sambongrejo Kec. Sumberrejo Regency of Bojonegoro. This research is a qualitative research that is descriptive research, which describes the existing phenomena through a scientific approach. The data collection techniques used by researchers are observation, interview and documentation methods. The data analysis technique used in this study includes data reduction (data reduction), data display (data presentation), conclution drwawing / verification. In accordance with the observations of researchers in the field that the forms of internalizing the values ​​of akhlakul karimah are morals towards Allah SWT, morals to the Prophet Muhammad, personal morals, morals in the family, social morals and national morals. The process of internalizing these akhlakul karimah values ​​through madrasah diniyah activities such as teaching and learning activities ta 'limul muta'aliim, tanbihul muta'aliim, tafsir, hadith. Praying in congregation khataman Al-Qur'an, istigosah, vasinan dziba'an and mukhadloroh These activities are applied in 4 methods, namely the habituation method, exemplary method, guidance method and motivation or encouragement method. And the result of the internalization process of the moral values ​​is that The spiritual improvement of students is already good, seen from the awareness of students in carrying out activities at Madrasah Diniyah and the growth of moral values ​​in students.